The Politics of Technocracy in Malaysia (1957-2012) - WEI LOH, JASON SEONG (Jurnal Studi Pemerintahan, 2016)
Malaysia’s technocracy (administrative elite) and the government of the day (political elite) have had and continue to enjoy a harmonious and symbiotic relationship. Such synergy had its origins and background in British colonial rule when promising Malays were groomed for administrative positions. The dawn ofmerdeka (national independence) allowed for the transition from administrativepositions to political leadership. The first three prime ministers, namely TunkuAbdul Rahman, Abdul Razak and Hussein Onn were drawn from these ranks.There was an organic development in the relationship between the ‘old’ technocrats and politicians expressed in shared strategic outlook and direction. As such, national development was characterised not by intermittent periods of political disruption but a sustained period of continuity in the pre-conditions for economic growth which extended and heightened throughout the premiership ofMahathir Mohamad. His successor, Abdullah Badawi, started to install corporatefigures as technocrats to professionalise the governance of the administrativesystem. Under Najib Razak the role of these ‘new’ technocrats was further entrenched and enhanced.